Acute low back pain: systematic review of its prognosis - Pengel, Liset H M (BMJ Publishing Group Ltd., 2003)
Objectives To describe the course of acute low back pain and sciatica and to identify clinically important prognostic factors for these conditions. Design Systematic review. Data sources Searches of Medline, Embase, Cinahl, and Science Citation Index and iterative searches of bibliographies. Main outcome measures Pain, disability, and return to work. Results 15 studies of variable methodological quality were included. Rapid improvements in pain (mean reduction 58% of initial scores), disability (58%), and return to work (82% of those initially off work) occurred in one month. Further improvement was apparent until about three months. Thereafter levels for pain, disability, and return to work remained almost constant. 73% of patients had at least one recurrence within 12 months. Conclusions People with acute low back pain and associated disability usually improve rapidly within weeks. None the less, pain and disability are typically ongoing, and recurrences are common.